Daily consumption of milk fat globule membrane plus habitual exercise improves physical performance in healthy middle-aged adults - Ota, Noriyasu (Springerplus, 2015)
Our recent studies demonstrated that habitual exercise plus dietary supplementation with milk fat globule membrane (MFGM) improved endurance capacity and muscle function by stimulating neuromuscular development in mice. The aim of this study was to investigate the efficacy of dietary MFGM supplementation plus habitual exercise on the physical performance of middle-aged Japanese adults in a pilot randomized, double-blind, placebo-controlled trial. Forty-four subjects (men, n = 22; women, n = 22) were randomly assigned into two groups: one received placebo tablets (placebo group, n = 22 [men, n = 11; women, n = 11]), while the other received MFGM tablets (MFGM group, n = 22 [men, n = 11; women, n = 11]). The subjects ingested either MFGM (1 g/day) or placebo (1 g/day of whole milk powder) tablets every day for the 10-week study period and engaged in an exercise training program twice per week. A physical function test was performed at baseline and at 5 and 10 weeks. A significant group-by-time interaction was found for the side step test, muscle cross-sectional area (CSA), and muscle fiber conduction velocity (MFCV). In the placebo group, there were no significant intragroup differences. In the MFGM group, side step score and muscle CSA were significantly greater at 10 weeks compared to the baseline, and MFCV was significantly higher than that in the placebo group at 10 weeks. The changes in percentage of the side step score, muscle CSA, and MFCV in the MFGM group were significantly higher than in the placebo group at 10 weeks. These results suggest that daily MFGM ingestion combined with regular exercise might enhance physical performance such as agility in middle-aged adults.